Features and Directions of Public Administration Development in the Context of Digital Transformation - Artem P. Rossikhin (Теория и практика общественного развития, 2026)
The article presents the results of a study of the features and directions of public administration development in modern conditions. Scientific and practical interest in this issue stems from ongoing transformations that are driving a digital shift in the role of public administration in ensuring the sustainable development of socio-economic systems in the digital environment. The digitalization of public services generates new, unpredictable risks; mitigating these risks contributes to the improvement of state economic and social policies. Transforma-tional changes are also evident within the public administration apparatus, where the government bodies adopt the “New Public Management” concept and transition towards an e-government model. The article aims to as-sess the current state of digital tools integration into the public administration system. The object of the study is the public administration system in Russia. The subject of research encompasses the characteristics and de-velopment trends of public administration in modern digital conditions. The results of the study make it possible to develop recommendations aimed at improving the effectiveness of the state institutions in managing the socio-economic sphere of Russia through a more comprehensive application of digital tools. Implementing these measures can act as a stimulating factor in enhancing public governance in social and economic policy, as well as for improving the quality of services provided to the citizens. For the Russian state, the chosen trajec-tory of socio-economic development is a fundamental factor in maintaining the conditions necessary to ensure the national security of Russia amid ongoing geopolitical and socio-economic turbulence.